A reflection on language politics at Nelson Mandela University. Issue 1 (23rd March 2018) - Mayaba, Nokhanyo Nomakhwezi
Abstract: Over the past two years, institutions of higher learning in South Africa have been sites of student protests. At the core of these protests were language politics which drew attention to theories of decoloniality and which challenged universities to examine their language policies and practices. Nelson Mandela University was no exception. In the Faculty of Education, in particular, it became clear that language debates should form part of ongoing conversations about a transformed and decolonised curriculum. Teaching and learning conversations had to be reimagined as 'talking spaces' with students. Using a critical pedagogy lens, this article seeks to provide an auto-ethnographic reflection on the language issues as revealed in student voices generally, during and after the protests. Moreover, this paper focuses on how the language politics has influenced thinking about strategies for developing a language policy at the university. It is argued that a language policy that does not address issues of social justice, equity and does not serve the needs of the diverse university community is problematic. Furthermore, a case is made that in order to make an effective contribution to debates on language politics, universities should aim to engage students as active participants as their voice can influence change.